Bickerstaff's brainstem encephalitis associated with anti-GM1 and anti-GD1a antibodies. Issue 9 (18th September 2020) - Cleaver, Jonathan; James, Richard; Chohan, Gurjit; Lyons, Paul
Abstract : Bickerstaff's brainstem encephalitis (BBE) is a Guillain-Barré syndrome (GBS) spectrum disorder associated with predominantly central nervous system predilection. Patients exhibit a variable constellation of depressed consciousness, bilateral external ophthalmoplegia, ataxia and long tract signs. Although the pathophysiology is not fully understood, it has been associated with anti-GQ1b antibodies in two-thirds of patients. We present a patient with clinical features consistent with BBE and positive anti-GM1 and anti-GD1a antibodies. A diagnostic approach to the acutely unwell patient with brainstem encephalitis is explored in this clinical context with a literature review of the aforementioned ganglioside antibody significance. Intravenous immunoglobulin therapy is highlighted in BBE using up-to-date evidence-based extrapolation from GBS.